Exploring the alleviating effects of Bifidobacterium metabolite lactic acid on non-alcoholic steatohepatitis through the gut-liver axis - Zhao, Hongmei; Zhou, Juan; Yuan, Lingzhi; Sun, Zhiyi; Liu, Yi; Zhao, Xinyu; Ye, Feng (Frontiers in Microbiology, 2025)
ObjectiveThis study investigates the protective effects of lactic acid, a metabolite of Bifidobacterium, on non-alcoholic fatty liver disease (NAFLD) induced by a high-sugar, high-fat diet (HFD) in mice, in the context of the gut-liver axis.MethodsA NAFLD mouse model was established using a HFD, and different intervention groups were set up to study the protective effects of Bifidobacterium and its metabolite lactic acid. The groups included a control group, NAFLD group, Bifidobacterium treatment group, Glyceraldehyde-3-P (G-3P) co-treatment group, and NOD-like receptor family pyrin domain containing 3 (NLRP3) overexpression group. The evaluation of liver function and lipid metabolism was conducted using the liver-to-body weight ratio, histological staining, and biochemical assays. Enzyme-linked immunosorbent assay (ELISA) was performed to measure inflammatory cytokines, and western blotting was used to analyze the expression of NLRP3 inflammasome and autophagy-related molecules. In vitro, an NAFLD cell model was established using oleic acid, with cells treated with lactic acid and NLRP3 overexpression to assess lipid droplet accumulation and inflammation.ResultsIn vivo findings indicated that, in comparison to CBX group (Control group without antibiotic treatment), NAFLD/CBX group (NAFLD group without antibiotic administration) and NAFLD/ABX group (NAFLD group with antibiotic administration) exhibited increased liver-to-body weight ratio, higher lipid droplet accumulation, aggravated liver histopathological damage, and elevated levels of AST (Aspartate Aminotransferase), ALT (Alanine Aminotransferase), TC (Total Cholesterol), TG (Triglycerides), LDL-C (Low-Density Lipoprotein Cholesterol), IL-6 (Interleukin-6), TNF-α (Tumor Necrosis Factor-alpha), IL-1β (Interleukin-1 beta), and NLRP3-related molecules, while HDL-C (High-Density Lipoprotein Cholesterol) levels significantly decreased. Intervention with Bifidobacterium significantly reversed these adverse changes. Further addition of G-3P led to more pronounced improvement in NAFLD symptoms, while overexpression of NLRP3 weakened the protective effects of Bifidobacterium. In vitro results indicated that Ole group exhibited heightened lipid droplet accumulation and expression of NLRP3 inflammasome-related molecules relative to the control group. Treatment with lactic acid effectively reversed these changes; however, the protective effect of lactic acid was significantly weakened with NLRP3 overexpression.ConclusionLactic acid can alleviate lipid metabolism disorders in NAFLD induced by diet through the inhibition of inflammation mediated by the NLRP3 inflammasome and the regulation of the autophagy process.